Analysis of Interlayer Connection Catastrophe Characteristics in Internet AS level Topology - Bo Yang; Hai Zhao; Jun Zhang; Jun Ai; Si-yuan Jia; Xin Ge; Wei Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Based on CAIDA’s (cooperative association for Internet data analysis) statistics at AS-level collected from April 2009 to April 2010, it is found that network size, degree correlations and clustering have changed significantly three times. According to the definition of k-core, the Internet topology is divided into different levels. In this paper, by analyzing the changing connection on each level at the three time spots, we found that the connection difference between the highest and the lowest level varies cyclically. Before Internet has significant change, the connection difference between the highest and the lowest shell changes acutely. At that time point it is the later stage of the fluctuation period which is the accumulation of small fluctuation. The concept of catastrophe coefficient is proposed for quantifying the probability of Internet catastrophe so that the catastrophe coefficient of Internet could be calculated on real time, and the catastrophe time spots could be predicted. Using real data for verification, it turns out that catastrophe coefficient can accurately predict the "giant fluctuations" occurrence in the macroscopic structure. With the proposal of the concept of catastrophe coefficient, the research can play an important guiding role in understanding the actual network internal development and changes, analyzing the cause of Internet catastrophe, preventing devastating catastrophe, planning and further re-designing Ipv6. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1978